Indigenous Wisdom for Developing Economic Life Case of Yokari People, West Papua - Blesia, Jhon Urasti; Ratang, Westim (KOMUNITAS: International Journal of Indonesian Society and Culture, 2016)
Natural resources need to be used to improve the economic life based on the indigenous local wisdom. This is one of Jayapura regency’s economic development programs to increase the welfare of the whole society as mandated by the special autonomy policy in West Papua. This study aims to address the potential of natural resources in Yokari customary council by utilising their local knowledge to improve the economic life of the community. The use of qualitative research and triangulation method for data collection and analysis are used and purposive sampling method employed to answer the expected objectives of this study. The head of village government, Ondowapona, elders and religious leaders were approached for in-depth interviews in addition to the observation and secondary data study that had been largely completed beforehand. The results show that the majority of community work as fishermen and farmers along with the potential of natural resources, being various kind of fish, fruit, and vegetable used for sale or daily consumption in the family. Local wisdom, such as the obligation to protect the environment and customary laws, restriction to fish with the bombs and taboo to work on Sunday are acknowledged and accounts for traditional sanctions that need to be highly considered by the community to engage with the natural resources. Significant challenges faced by the community, such as difficult access to transportation, marketing and distribution channels of their resources need to be seriously taken into account by the government to improve a better quality of the community life.